Analysis of the Legal Strength of Using Closed Circuid Television in Proving Crimes of Theft - Handika, Ahmad; Puluhulawa, Jufryanto (Estudiante Law Journal, 2024)
This research aims to determine the legal strength of the use of closed circuit television in proving criminal acts of theft. This research is normative legal research with a statutory approach and a conceptual approach which is then formulated systematically so that it provides an overview and is processed by researchers using descriptive analysis techniques. The results of the research show that the use of CCTV (closed circuit television) recordings in general crimes as electronic evidence cannot be used as stand-alone evidence in the Criminal Procedure Code because the Criminal Procedure Law only recognizes five tools. evidence as contained in Article 184, added to the evidence using the Negatief Wettelijk theory of evidence where the judge may only pass judgment based on valid evidence by the provisions in the Criminal Procedure Code for general crimes